O egalitaryzmie ekonomicznym - Załuski, Wojciech (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2016)
Economic egalitarianism, i.e., the view according to which equality of resources is a social value, has two different forms: the intrinsic and the instrumental. According to the former economic equality is a value in itself (i.e., an ‘intrinsic’ value), whereas according to the latter it is an ‘instrumental’ value, i.e., it is a value in so far as it contributes to the realization of some other values (which, as opposed to equality, are intrinsic), such as, e.g. the alleviation of suffering, higher quality of life, political freedom, or fraternity. Intrinsic egalitarianism is a controversial view, as it is susceptible to the famous ‘levelling down’ objection (formulated by Derek Parfit). We formulate in the paper two main arguments for the view that instrumental egalitarianism is not plausible as well. The first argument says that it is difficult to demonstrate that social and health problems conceived by the adherents of instrumental economic egalitarianism (such as, e.g., Richard Wilkinson and Kate Pickett) as the effects of inequalities of resources are really caused by these inequalities; we argue that it is more plausible, at least with regard to some of these effects, to maintain that their cause is poverty (and thereby the low absolute, rather than relative, level of income). According to the second argument, even if the adherents of instrumental economic egalitarianism are right in claiming that there exists a causal link between economic inequalities and social and health problems, it would not be sufficient to morally justify their egalitarian view, since the link is to a large extent based upon morally dubious psychological mechanisms, such as envy or the proclivity to overestimate the importance of material resources. Finally, we argue that the view which best harmonizes with the above critique of egalitarianism is the ‘doctrine of sufficiency’ proposed by Harry Frankfurt, which implies that what is important is not equality of resources but that all persons have enough of them.
On economic egalitarianism
Keywords: economic equality; priority; levelling down; homo socialis; poverty; sufficiency